Godzilla [videorecording (DVD)] - Olsen, Elizabeth, 1989-; Cranston, Bryan, 1956-; Watanabe, Ken, 1959-; Binoche, Juliette, 1964-; Strathairn, David (Warner Bros. Entertainment, 2014)
From visionary new director Gareth Edwards comes a powerful story of human courage and reconciliation in the face of titanic forces of nature, when the awe-inspiring Godzilla rises to restore balance as humanity stands defenseless.